Evaluation of doubled haploid rice lines for agronomic performance and resistance to bacterial leaf blight - ISWARI SARASWATI DEWI; RATNA KARTIKA PUTRI; BAMBANG SAPTA PURWOKO; SITI YURIYAH; ISKANDAR LUBIS (Society for Indonesian Biodiversity, 2024)
Abstract. Dewi IS, Putri RK, Purwoko BS, Yuriyah S, Lubis I. 2024. Evaluation of doubled haploid rice lines for agronomic performance and resistance to bacterial leaf blight. Biodiversitas 25: 4275-4283. The dynamic of climate change aggravates the adverse effect of biotic stress. The biotic stresses affecting rice fields include bacterial leaf blight (BLB) caused by Xanthomonas oryzae pv. oryzae (Xoo). This research evaluated the agronomic performance and resistance of doubled haploid (DH) rice lines against three dominant Xoo pathotypes in Indonesia (i.e., pathotype groups III, IV, and VIII). Nineteen rice genotypes consisting of 14 advanced DH lines, two commercial varieties (Ciherang and Inpari 18), and three BLB checks (IRBB-66 as resistant check, IR-64 and TN-1 as susceptible check) were assessed against three dominant Xoo pathotypes in Indonesia following the SES for rice from IRRI. Results indicated that 11 DH lines, except M-1, M-4, and M-14 had good agronomic traits, including productivity over 8 tons ha-1, significantly higher than Inpari 18. The varying severity of BLB was influenced considerably by pathotype, genotype, and pathotype-genotype interaction. The disease severity from each pathotype was relatively the same across two inoculation times (vegetative and generative phase). In both growth phases, all DH rice lines, except for M-5 and M-13 were categorized as resistant against pathotypes III and IV. These findings have practical implications for developing disease-resistant rice varieties, enhancing the relevance and applicability of the research.